2009
DOI: 10.1038/npp.2009.213
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Val66Met is Associated with Introversion and Interacts with 5-HTTLPR to Influence Neuroticism

Abstract: Brain-derived neurotrophic factor (BDNF) regulates synaptic plasticity and neurotransmission, and has been linked to neuroticism, a major risk factor for psychiatric disorders. A recent genome-wide association (GWA) scan, however, found the BDNF Val66Met polymorphism (rs6265) associated with extraversion but not with neuroticism. In this study, we examine the links between BDNF and personality traits, assessed using the Revised NEO Personality Inventory (NEO-PI-R), in a sample from SardiNIA (n ¼ 1560) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
83
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 68 publications
(123 reference statements)
9
83
2
Order By: Relevance
“…These findings suggest that the BDNF Val66Met polymorphism does not have a direct effect on AS. This finding is in line with studies that have found no significant direct association between BDNF Val66Met polymorphism and personality traits such as neuroticism or harm avoidance and anxiety disorders or mood disorders, including OCD, panic disorder, PTSD and depression (Arias et al, 2012; Chen et al, 2013; Frustaci et al, 2008; Hong et al, 2012; Minelli et al, 2011; Surtees et al, 2007; Terracciano et al, 2010), despite some studies reporting such associations (Frustaci et al, 2008; Lang et al, 2005; Min et al, 2013; Montag et al, 2010; Sen et al, 2003; Terracciano et al, 2010). Firstly, the grouping of Met66 allele carriers (i.e.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These findings suggest that the BDNF Val66Met polymorphism does not have a direct effect on AS. This finding is in line with studies that have found no significant direct association between BDNF Val66Met polymorphism and personality traits such as neuroticism or harm avoidance and anxiety disorders or mood disorders, including OCD, panic disorder, PTSD and depression (Arias et al, 2012; Chen et al, 2013; Frustaci et al, 2008; Hong et al, 2012; Minelli et al, 2011; Surtees et al, 2007; Terracciano et al, 2010), despite some studies reporting such associations (Frustaci et al, 2008; Lang et al, 2005; Min et al, 2013; Montag et al, 2010; Sen et al, 2003; Terracciano et al, 2010). Firstly, the grouping of Met66 allele carriers (i.e.…”
Section: Discussionsupporting
confidence: 87%
“…Further support for the aforementioned is reflected in findings of gene x gene and gene x gene x environment interactions which are indicative of significant interaction effects of the BDNF Val66Met polymorphism and the serotonin transporter gene ( SLC6A4 ) on anxiety-related traits (e.g. neuroticism and harm avoidance) (Arias et al, 2012; Terracciano et al, 2010) and depressive symptoms and disorder (Gutiérrez et al, 2015; Kaufman et al, 2006). Finally, the effects of environmental influences other than CM, such as parenting rearing practices (Ibarra et al, 2014) and general self-efficacy (Schiele et al, 2016), on AS should be explored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with this, a positron emission tomography (PET) study of 25 healthy individuals showed that the val/val genotype was associated with increased SERT binding in men (Henningsson et al, 2009). In addition, a val66met interaction with the 5-HTTLPR (5-HT-transporter-linked promoter region) polymorphism in relation to neuroticism (a risk factor for developing major depression) has been reported (Terracciano et al, 2010).…”
Section: Introductionmentioning
confidence: 99%